Studying the effect of reinforcing by fibers and particles on mechanical properties for polymer Matrix composite materials - Ibrahim A. Atiyah, (Journal of engineering sciences and information technology, 2017)
The using of polymer matrix composite materials has found a wide range of applications in our modern day world. This is as a result of the combination of characteristics which are achieved by these materials. This work aimed on the preparation of polymeric-matrix composite material in order to improve its mechanical properties by using more than one type of reinforcement with different volume fraction values. This composite materials prepared from unsaturated polyester resin as a matrix, reinforced by E-glass fiber with (5%) volume fraction and graphite particles of (1%, 3%, 5%,7% and 10%) volume fractions, and study  the effect of these fillers on the  properties of polyester. The reinforcing by different types of materials with different values of volume fraction led to improve the mechanical properties (i.e. tensile strength, modules of elasticity and hardness) significantly, because of the contribution of both graphite particles and glass fibers to bear the applied load, also due to the high hardness graphite particles